Model Template Business Plan dalam Menyiapkan Selling Document Business Matching Pemberdayaan UMKM Juara Kota Bandung - Wahyuni, Ning; Harto, Budi (Jurnal Pengabdian Tri Bhakti, 2020)
There is a need for small and medium business actors to make business planning proposals (Business Plan) in the framework of Business Matching aimed at obtaining funding / capital and other access, can be synergized between business players and investors (pitching) Where in the field, most SMEs do not understand the problem of financial planning with technology. UKM players who do not recognize Excel functions will be facilitated because the required formulas have been included in the related templates. In addition, SMEs that also do not understand accounting in making financial projections will easily present the required financial projections, because the template adapts the necessary accounting concepts, which is integrated in the formula provided. Therefore, this template model is suitable for use by SMEs who do not understand accounting in producing financial reports, also suitable for SMEs who are just starting to take advantage of technology using the Excel application in managing financial data, but do not yet know how to integrate recorded data into financial statement figures. The results of the empowerment of SMEs have shown enthusiasm in making Business Plans based on proper accounting and financial management provisions and can be practiced directly by business actors. The impact of using this Business Plan Template Model can increase the independence of SMEs in making their business plans, used for other needs and as a means of controlling the resources used.